Efficacy and safety of ciprofol for gastroscopy in patients with obesity: a randomised clinical controlled trial using different weight-based dosing scales - Danru Xie; Yanjing Zhang; Feifei Li; Yaoheng Yang; Mengjiao Che; Geng Li; Yiwen Zhang (BMC Anesthesiology)
Abstract Background This study aimed to compare the efficacy and safety of ciprofol-induced doses based on three indices: total body weight (TBW), ideal body weight (IBW), and lean body weight (LBW) in patients with obesity undergoing gastroscopy. Methods In a single-centre, prospective, randomised study conducted at an endoscopy centre, a total of 108 patients aged 18–65 years who underwent painless gastroscopy and had a body mass index (BMI) of 28–39.9 kg/m2 were included. Patients with obesity from the intended study population were randomised to receive a ciprofol infusion (0.4 mg/kg) for the induction of anaesthesia based on TBW (Group T), IBW (Group I), or LBW (Group L). A Modified Observer’s Assessment of Alertness/Sedation (MOAA/S) scale score of < 1 was considered a marker of loss of consciousness, prompting gastroscopy. The primary outcomes were the success rate of anaesthesia for the procedures, and that of general anaesthesia achieved using the initial dose. Secondary outcomes included the frequency of remedial sedation, total ciprofol dose, and adverse events Results The procedure success rate was 100% in all three groups. Compared to Group L, the general anaesthesia success rate achieved with the initial dose was higher and the frequency of remedial sedation was lower in Groups T and I. Compared to Group L, fewer patients in Group T required additional medication. Compared to Group T, the occurrence of hypoxaemia was lower in the remaining two groups, and Group L had a lower incidence of posterior tongue drops and hypotension. Conclusions Induction doses of ciprofol based on TBW or IBW provided better anaesthesia than doses based on LBW for gastroscopy in patients with obesity. LBW-based induction doses of ciprofol improved cardiovascular stability and respiratory safety, whereas IBW-based induction doses of ciprofol reduced respiratory depression. Trial registration This study was registered in the Chinese Clinical Trial Registry (ChiCTR2300073539 first registration date 13/07/2023).